Recent Advances in Pharmacotherapy Development for Abdominal Aortic Aneurysm - Koichi Yoshimura; Hiroki Aoki (International Journal of Vascular Medicine)
Abdominal aortic aneurysm (AAA) is a common disease causing segmental expansion and rupture of the aorta with a high mortality rate. The lack of nonsurgical treatment represents a large and unmet need in terms of pharmacotherapy. Advances in AAA research revealed that activation of inflammatory signaling pathways through proinflammatory mediators shifts the balance of extracellular matrix (ECM) metabolism toward tissue degradation. This idea is supported by experimental evidence in animal models that pharmacologic intervention at each pathological step can prevent AAA development. Previously, we identified c-Jun N-terminal kinase (JNK), a pro-inflammatory signaling molecule, as a therapeutic target for AAA. Abnormal activation of JNK in AAA tissue regulates multiple pathological processes in a coordinated manner. Pharmacologic inhibition of JNK tips the ECM balance back towards repair rather than degradation. Interventions targeting signaling molecules such as JNK in order to manipulate multiple pathological processes may be an ideal therapeutic strategy for AAA. Furthermore, the development of biomarkers as well as appropriate drug delivery systems is essential to produce clinically practical pharmacotherapy for AAA.